Autonomically-mediated decrease in microvascular blood flow due to mental stress and pain in sickle cell disease: A target for neuromodulatory interventions. (March 2020) - Martin, Sarah R.; Shah, Payal; Denton, Christopher; Zeltzer, Lonnie K.; Veluswamy, Saranya; Khoo, Michael C.K.; Coates, Thomas D.
Highlights: Pain and stress cause observable, physiological changes associated with SCD crisis. Youth with SCD vasoconstrict, reducing blood flow during pain, fear, and stress. Vasoconstriction can be quantified using readily available sensors and analyses. Engagement in hypnosis may offset harmful microvascular responses to acute pain. "Stress" causes measurable and disease-modifying tissue perfusion changes. Abstract: Pain and vaso-occlusive crises (VOC) are hallmark complications of sickle cell disease (SCD) and result in significant physical and psychosocial impairment. The variability in SCD pain frequency and triggers for the transition from steady state to VOC are not well understood. This paper summarizes the harmful physiological effects of pain and emotional stressors on autonomically-mediated vascular function in individuals with SCD and the effects of a cognitive, neuromodulatory intervention (i.e. hypnosis) on microvascular blood flow. We reviewed recent studies from the authors' vascular physiology laboratory that assessed microvascular responses to laboratory stressors in individuals with SCD. Results indicate that participants with SCD exhibit marked neurally mediated vascular reactivity in response to pain, pain-related fear, and mental stress. Further, pilot study results show that engagement in hypnosis may attenuate harmful microvascular responses to pain. The collective results demonstrate that autonomically-mediated vascular responses to pain and mental stress represent an important SCD intervention target. This ongoing work provides physiological justification for the inclusion of cognitive, neuromodulatory and complementary treatments in SCD disease management and may inform the development of targeted, integrative interventions that prevent the enhancement of autonomic vascular dysfunction in SCD.